Faktor-Faktor yang Berhubungan dengan Imunisasi Tetanus Toxoid pada Ibu Hamil di Puskesmas Tanah Jambo Aye Aceh Utara Tahun 2024 - Rusvita Rusvita; Ester Simanullang (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Pregnancy is a reproductive process that needs special care so that it runs well, because pregnancy contains the life of both the mother and fetus. In Indonesia, the number of AKI in 2020 showed 4,627 cases of death, most of the causes of maternal death were caused by other causes at 34.2%, bleeding at 28.7%, hypertension in pregnancy at 23.9%, and infection at 4.6%. %.The aim of this research is to find out what factors are related to tetanus toxoid immunization in pregnant women at the Jambo Aye Health Center, North Aceh. This type of research is a survey type with a cross sectional design. The number of research samples is 60 pregnant women. The research results show that age is = 0.024 < sig a value = 0.05, this proves that there is a relationship between age and the mother's attitude towards TT immunization. Parity is = 0.021 > sig a value = 0.05, this proves that there is no relationship between parity and the mother's attitude towards TT immunization. Education is = 0.032 < sig a value = 0.05, this proves that there is a relationship between education and the mother's attitude towards TT immunization. Knowledge is = 0.021 < sig a value = 0.05, this proves that there is a relationship between knowledge and the mother's attitude towards TT immunization. Providing Health Socialization is = 0.041 < sig a value = 0.05, this proves that there is a relationship between Providing Health Socialization and the mother's attitude towards TT immunization. So it can increase knowledge and learning experiences, especially about the factors that influence pregnant women to carry out TT immunization.